2011
DOI: 10.1093/annhyg/meq096
|View full text |Cite
|
Sign up to set email alerts
|

Total Inward Leakage of Nanoparticles Through Filtering Facepiece Respirators

Abstract: Nanoparticle (<100 nm size) exposure in workplaces is a major concern because of the potential impact on human health. National Institute for Occupational Safety and Health (NIOSH)-approved particulate respirators are recommended for protection against nanoparticles based on their filtration efficiency at sealed conditions. Concerns have been raised on the lack of information for face seal leakage of nanoparticles, compromising respiratory protection in workplaces. To address this issue, filter penetration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 37 publications
(42 reference statements)
0
25
0
2
Order By: Relevance
“…The cited study did not detect an MPPS for wood and paper aerosols due to multiple peaks in the TILdnormalp curves. Previous TIL studies have focused on N95 FFRs or surgical masks, for which the particle size effect was found significant and the TIL values were close to the penetration levels observed for the filters only (Myers et al , 1991; Cho et al , 2010a; Rengasamy and Eimer, 2011). At the same time, little information has been generated with respect to the MPPS for face seal leakage.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…The cited study did not detect an MPPS for wood and paper aerosols due to multiple peaks in the TILdnormalp curves. Previous TIL studies have focused on N95 FFRs or surgical masks, for which the particle size effect was found significant and the TIL values were close to the penetration levels observed for the filters only (Myers et al , 1991; Cho et al , 2010a; Rengasamy and Eimer, 2011). At the same time, little information has been generated with respect to the MPPS for face seal leakage.…”
Section: Resultsmentioning
confidence: 52%
“…At the same time, little information has been generated with respect to the MPPS for face seal leakage. When testing N95 FFRs with artificially created cylindered leaks, Rengasamy and Eimer (2011) found that for leak diameters ≤1.65 mm, the MPPS was ~50 nm; we believe that this value likely represents the N95 filter penetration, whereas the TIL of the respirator used in this study (equipped with P100 filters) is primarily governed by the face seal leakage penetration. This likely explains the suppressed peaks or the plateaus seen in the curves presented in Fig.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…It is acknowledged that the filtration efficiency of P100 rated filters is higher than that of N95 rated filters for nanoparticles. However, contribution from the faceseal leakage could be higher for P100 respirators (both FFR and EHR) due to higher breathing resistance (pressure drop) versus N95 respirators [ 19 ] , although there is some debate [ 20 ] . As a result, the performance for P100 respirators (i.e., any FFR or EHR with aP100 filter) may be similar to the N95 respirators 1 if the respirator does not seal well.…”
Section: Introductionmentioning
confidence: 99%